2007
DOI: 10.1111/j.1365-2427.2007.01871.x
|View full text |Cite
|
Sign up to set email alerts
|

Testing the differential predation hypothesis for the invasion of rusty crayfish in a stream community: laboratory and field experiments

Abstract: 1. We tested the hypothesis that the non-native rusty crayfish (Orconectes rusticus) is less vulnerable to predators than two native species (O. propinquus and O. obscurus) it is replacing in streams of the upper Susquehanna River catchment (New York, U.S.A.). 2. We used laboratory experiments to compare species-specific predation rates by smallmouth bass (Micropterus dolomieu) on crayfish of equal size and field tethering experiments to compare relative predation rates between native O. propinquus and nonnati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 65 publications
(153 reference statements)
0
18
0
Order By: Relevance
“…In order to obtain information on population dynamics a suitable observation method, which does not influence survival, growth and behaviour, is crucial. Mark and recapture methods are widely used in field (Abrahamsson, 1973;Guan, 1997;Bubb et al, 2002) and laboratory (Guan and Wiles, 1996;Barki et al, 1997;Kuhlmann et al, 2008) experiments on crayfish. Objectives of the present study were: (1) to evaluate four different marking methods for O. limosus (tag retention and readability, effects of tagging on survival); (2) to evaluate the effect of tagging on moult increments, and to observe the relationship with number of moults.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain information on population dynamics a suitable observation method, which does not influence survival, growth and behaviour, is crucial. Mark and recapture methods are widely used in field (Abrahamsson, 1973;Guan, 1997;Bubb et al, 2002) and laboratory (Guan and Wiles, 1996;Barki et al, 1997;Kuhlmann et al, 2008) experiments on crayfish. Objectives of the present study were: (1) to evaluate four different marking methods for O. limosus (tag retention and readability, effects of tagging on survival); (2) to evaluate the effect of tagging on moult increments, and to observe the relationship with number of moults.…”
Section: Introductionmentioning
confidence: 99%
“…If this relationship is similar for O. palmeri, warmer temperatures would be more favorable for O. palmeri growth and cooler temperatures would be more favorable for P. spiculifer growth. Rapid growth is important for crayfish fitness, because larger crayfish are more likely to avoid fish predation and displace smaller crayfish from shelter (Butler and Stein 1985;Garvey and Stein 1993;Hill et al 1993;Mather and Stein 1993;Kuhlmann et al 2008). Average fall temperatures in the Flint mainstem are close to the thermal preferendum of O. palmeri and those in the tributaries are close to the thermal preferendum of P. spiculifer (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies have found fish predation to be important in structuring crayfish distributions and in affecting crayfish population sizes (Chucholl et al 2008;Dorn 2008). In addition, previous research indicates that small crayfish are more susceptible than large crayfish to predation from fish (Didonato and Lodge 1993;Garvey and Stein 1993;Kuhlmann et al 2008) and that YOY crayfish may be absent from an area due to selective fish predation even when the adults are still present (Fortino and Creed 2007). P. spiculifer may compete with small O. palmeri for shelter in the downstream area, exposing O. palmeri to fish predators.…”
Section: Discussionmentioning
confidence: 94%
“…It can invade both lakes and streams where it displaces native congeners (Capelli 1982;Hill and Lodge 1999;Wilson et al 2004) because of its higher fecundity, earlier reproduction, and faster growth of eggs and young-of-year compared with native species (i.e., Orconectes propinquus or Orconectes virilis) (Lodge et al 1985;Olsen et al 1991). Rusty crayfish is also more aggressive (Capelli and Munjal 1982), has a higher ingestion rate of snails (Olsen et al 1991), and is less sensitive to predation by fish (DiDonato and Lodge 1993;Hill and Lodge 1995;Kuhlmann et al 2008). As a result, it has been shown to displace native species both by competition for refuges (Hill and Lodge 1994) and by hybridization (Perry et al 2001).…”
Section: Introductionmentioning
confidence: 97%